A Comparative Analyses of Form and Style in the Works of Suowari Jacqueline and Ibim Cookey - Stewart, Ashley; Fawara, Silver (Universitas Ciputra, 2025)
This study delves into the artistic realms of Jacqueline Suowari and Ibim Cookey, two remarkable Nigerian visual artists who have carved their unique paths within the contemporary art landscape. Suowari's masterful ball pen artistry and mixed media approach juxtaposed with Cookey's photorealistic pencil renderings, offering a captivating exploration of form and style. Through a meticulous examination of their biographies, creative processes, and 5 works each, totaling 10 artistic expressions, this study aims to unravel the profound narratives embedded within their works. Employing qualitative research methodologies, including library research and critical analysis, this paper navigates the intricate layers of identity, cultural heritage, and socio-political commentary that permeate Suowari's and Cookey's oeuvres. By dissecting the symbolic representations, technical mastery, and thematic underpinnings, this research illuminates the multifaceted roles these artists play in shaping contemporary Nigerian art discourse. Moreover, it delves into the ways in which their artworks serve as potent vehicles for challenging perceptions, fostering dialogue, and celebrating the resilience and beauty of the African diaspora. The research design utilizes both observational and survey methods, while data analysis is conducted using the semiotic descriptive approach. Among various similarities and distinctions, it was revealed that both artists engage in mixed media exploration, indicating the depth and diversity of their artworks. Ultimately, this comprehensive exploration seeks to contribute to the growing body of knowledge surrounding Nigerian visual arts while offering a nuanced appreciation for the transformative power of artistic expression.